Distribution and prognostic impact of different heart failure etiologies in patients with heart failure with mildly reduced ejection fraction - Schupp, Tobias; Schmitt, Alexander; Lau, Felix; Reinhardt, Marielen; Abel, Noah; Abumayyaleh, Mohammad S. A.; Ayoub, Mohamed; Mashayekhi, Kambis; Akın, Muharrem; Rusnak, Jonas; Weidner, Kathrin; Akın, Ibrahim; et al. (European journal of internal medicine, 2024)
Objective - The study investigates the characteristics and prognostic impact of different heart failure (HF) etiologies in patients with heart failure with mildly reduced ejection fraction (HFmrEF). - Background - Data regarding the characterization of patients with HFmrEF and their outcomes is scarce. - Methods - Consecutive patients with HFmrEF (i.e., left ventricular ejection fraction 41-49 % and signs and/or symptoms of HF) were retrospectively included at one institution from 2016 to 2022. Patients with ischemic cardiomyopathy (ICM) were compared to patients without ischemic cardiomyopathy (non-ICM). The primary endpoint was all-cause mortality at 30 months (median follow-up). Statistical analyses included Kaplan-Meier, multivariable Cox proportional regression analyses and propensity score matching. - Results - From a total of 1,832 patients hospitalized with HFmrEF, ICM was the most common HF etiology in 68.7 %, followed by hypertensive (9.7 %) and primary non-ischemic cardiomyopathies (NICM) (8.1 %). Within the entire study cohort, the presence of ICM was not associated with the risk of all-cause mortality (HR = 0.864; 95 % CI 0.723 - 1.031), however after multivariable adjustment (HR = 0.792; 95 % CI 0.646 - 0.972; p = 0.026) and propensity score matching (25.7% vs. 31.4 %; log rank p = 0.050), the presence of ICM was associated with lower risk of all-cause mortality at 30 months compared to patients without ICM. - Conclusion - ICM is the most common etiology of HF in HFmrEF and may be associated with favorable outcomes. This may be related to better adherence to pharmacological treatment and improved revascularization strategies for HFmrEF patients with ICM.